2022
DOI: 10.1038/s41598-022-08717-9
|View full text |Cite
|
Sign up to set email alerts
|

Delignification efficiency of various types of biomass using microwave-assisted hydrotropic pretreatment

Abstract: The use of a method of an effective delignification of lignocellulosic biomass is a key stage of designing processes of its microbiological conversion e.g. for the purposes of the production of cellulosic ethanol. The study was aimed at evaluating the effectiveness of microwave-assisted hydrotropic pretreatment using sodium cumene sulfonate (NaCS) for the delignification of pine and beech chips and wheat straw. Research results presenting the impact of process parameters of microwave-assisted hydrotropic delig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…However, to make the process economically viable, the selectivity must be increased, the pretreatment time reduced, and the chemicals recycled [ 41 , 45 ]. Furthermore, by separate usage or combining the alkaline treatment with physical techniques, such as microwave [ 46 , 47 , 48 , 49 ], ultrasound irradiation [ 18 , 19 , 41 , 49 , 50 , 51 ], or freeze–thaw (FT) cycles [ 44 , 47 , 52 ], the alkaline extraction can be improved even further taking into account the final objectives.…”
Section: Introductionmentioning
confidence: 99%
“…However, to make the process economically viable, the selectivity must be increased, the pretreatment time reduced, and the chemicals recycled [ 41 , 45 ]. Furthermore, by separate usage or combining the alkaline treatment with physical techniques, such as microwave [ 46 , 47 , 48 , 49 ], ultrasound irradiation [ 18 , 19 , 41 , 49 , 50 , 51 ], or freeze–thaw (FT) cycles [ 44 , 47 , 52 ], the alkaline extraction can be improved even further taking into account the final objectives.…”
Section: Introductionmentioning
confidence: 99%
“…20%) and wheat straw (a reduction by ca. 45%) biomasses, but the results presented herein indicate that the application of a higher pressure significantly intensifies the process of the lignin removal [ 28 ]. Microwave-assisted pretreatment was conducted for 60 min, because in our earlier study delignification of different types of lignocellulosic biomass was conducted using microwaves and NaCS for 15, 30 and 60 min.…”
Section: Resultsmentioning
confidence: 99%
“…The extension of the duration of pretreatment from 15 to 60 min at 117 PSI resulted in an increase in the level of delignification, which increased the reduction of the content of lignins from 12.21 to 36.58% in pine chips biomass, from 22.49 to 57.68% in beech chips biomass and from 25.43 to 74.08% in wheat straw biomass. The coefficient of regression of the growth of the level of reduction of the lignin content over time in lignocellulosic biomass of different origin ranged from 0.8485 to 0.9679 [ 28 ]. Other authors have indicated that pretreatment using microwave radiation and 0.75% w/v NaOH leads to a reduction of lignin content by ca.10% in the biomass of catalpa sawdust [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The details of the Klason lignin method and the UV-vis spectroscopic method are described in the ESI Method S4. † On the basis of the LP value determined by either the Klason lignin or the UV-vis spectroscopic method, the change in the LP of each sample was calculated according to eqn (3), 39 where LP 0 is the initial LP of MBW, and LP is the LP of each sample.…”
Section: Methodsmentioning
confidence: 99%